'A Bastion of Colonialism': Public Perceptions of the British Museum and its Relationship to Empire. Issue 4 (3rd September 2019) - Frost, Stuart
Abstract: This article uses visitor research to explore public attitudes to the British Museum and perceptions of its relationship to the history of the British Empire. Firstly, it provides an analysis of direct messages received by the Museum over a twelve month period via letters, emails and comments on social media platforms. Secondly, it draws on short interviews undertaken with visitors upon arrival at the Museum before entry. Thirdly, it draws on formative and summative evaluation for two recent British Museum special exhibitions that explicitly addressed imperial and colonial histories, 'Indigenous Australia: Enduring Civilization' (23 April – 2 August 2015) and South Africa: The Art of a Nation' (27 October 2016–26 February 2017). Finally, it draws on focus groups (April 2018) held to explore perceptions of the Museum held by culturally active non-visitors. Collectively this insight highlights the Museum's vast potential to inform contemporary debates about empire by developing new approaches to displaying and interpreting its collection.